Eficiência da aplicação de insumos a taxa variável na correção do solo e uniformização da produtividade da cultura da soja através de mapas de agricultura de precisão - Santi, Olavo Gabriel Rossato (2013)
The use of tools and techniques of precision agriculture by farmers is not a new in the field, because their uses are increasing year after year. Among them have been highlighted soil samples using the handheld GPS and yield maps as tools for identifying soil variability and production. In order to verify the efficiency of the variable fertilizers rates in improving of the soil fertility and productivity reflexes. The research was conducted in the Coxilha city, in the Rio Grande do Sul State, in a crop with no tillage system consolidated for over 15 years. The soil is a dystrophic Red Hapludox. The climate is humid subtropical Cfa, in according to the Köppen classification. Initially, in 2011, were vectorized with GPS navigation, 51.05 hectares and generated 35 compounded samples of soil, on a sampling grid of 1.5 hectares, to evaluate the chemical variability of the soil. Was used the software Campeiro CR 7 to generate the maps of chemical attributes. The same procedure was repeated in 2012 to verify the effects of soil corrections. The yield maps were obtained in soybean seasons of 2005, 2008, 2011, 2012 and 2013, and were generated with the help of the Ag Leader SMS software. After, correlations were made between fertility and productivity for the years 2011, 2012 and 2013. The results showed that the use of the soil sampling loop was effective for identify the variability in the soil fertility attributes and the effects of interventions in the variable rate. To the yield maps, it was verified no decreases in the variability of harvest after the nutrients variable rate corrections. It was possible to define regions with consistent productivity using the superposition of several yeld maps technique. The nutrient that most evolved, after the soil corrections, was the phosphorus and the same had the highest correlation with yield for the years 2012 and 2013.